Drug Management Evaluation with Hanlon Method and Fishbone Diagram - Desti Nuryani Sitompul; Opstaria Saptarini; Tri Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pharmaceutical management at primary health centers plays an important role in ensuring the availability, affordability, and quality of healthcare services. However, many primary health centers still face challenges in the planning, procurement, and evaluation of medicines, which potentially lowers the quality of services. This study aims to evaluate the quality of pharmaceutical management at Puskesmas X in Karanganyar Regency, determine priority problems using the Hanlon method, and analyze root causes with a Fishbone diagram. The study used an observational design with a qualitative descriptive and analytical approach. Data were collected through observation, interviews with pharmaceutical personnel, and document reviews of medicine management for the period December 2023–December 2024. The collected data were systematically examined through content analysis to identify key themes and patterns related to pharmaceutical management practices. Quantitative scoring of issues was performed using the Hanlon method to prioritize problem areas based on criteria such as magnitude, seriousness, and feasibility. Root cause analysis was conducted by categorizing identified problems into groups using the Fishbone diagram framework, facilitating the identification of underlying factors. The results show that the aspects of planning, procurement, stock, and evaluation did not meet standards, while the aspects of storage and medicine use were in accordance with standards. Hanlon method analysis identified medicine proposals based on FORNAS as the main priority issue, followed by the appropriateness of medicines with FORNAS, DOEN, fund allocation, and disease patterns. Fishbone analysis revealed the main causes as limitations in human resources, absence of SOPs, weak cross-sector coordination, and minimal technological support. The study concludes that improving human resource capacity, developing SOPs, forming proposal teams, strengthening coordination, and utilizing information technology are necessary to improve the quality of pharmaceutical management and ensure medicine availability according to community needs.